Odpowiedzi

2012-08-06T09:54:34+02:00

(x³-x²-3x-9):(x-3)=x²+2x+3

-x³+3x²

---------

     2x²-3x

    -2x²+6x

----------------

            3x-9

           -3x+9

       -----------

             =  =

 

(x-3)(x²+2x+3)=0

x-3=0 lub x²+2x+3=0

x=3      Δ=4-4*3=-8<0⇒brak pierwiastkow

 

Odp. x=3

2012-08-06T09:56:30+02:00

 x³ - x² - 3x -9 = 0

z wt. bezouta:

 x³ - x² - 3x -9 = (x²+2x+3)(x-3)

więc:

x²+2x+3 = 0          U           x-3=0

Δ=4-12=-8                           x=3

Δ<0 , brak rozw.           

 

 odp:

x=3